Same/different concept learning by primates and birds - Wright, Anthony A.; Kelly, Debbie M.; Katz, Jeffrey S. (Learning & behavior, 2021)
Same / different -concept learning experiments were conducted with two primate species and three avian species by progressively increasing the size of the training stimulus set of distinctly different pictures from eight to 1,024 pictures. These same / different learning experiments were trained with two pictures presented simultaneously. Transfer tests of same and different learning employed interspersed trials of novel pictures to assess the level of correct performance on the very first time of subjects had seen those pictures. All of the species eventually performed these tests with high accuracy, contradicting the long-accepted notion that nonhuman animals are unable to learn the concept of same / different . Capuchin and rhesus monkeys learned the concept more readily than did pigeons. Clark’s nutcrackers and black-billed magpies learned as readily as monkeys, and even showed a slight advantage with the smallest training stimulus sets. Those tests of same / different learning were followed by delay procedures, such that a delay was introduced after the subjects responded to the sample picture and before the test picture. In the sequential same/different task, accuracy was shown to diminish when the stimulus on a previous trial matched the test picture previously shown on a different trial. This effect is known as proactive interference . The pigeons’ proactive interference was greater at 10-s delays than 1-s delays, revealing time-based interference. By contrast, time delays had little or no effect on rhesus monkeys’ proactive interference, suggesting that rhesus monkeys have better explicit memory of where and when they saw the potential interfering picture, revealing better event-based memory.